A transcriptional and proteomic survey of Arachnocampa luminosa (Diptera: Keroplatidae) lanterns gives insights into the origin of bioluminescence from the Malpighian tubules in Diptera. (10th February 2015) - Silva, J. R.; Amaral, D. T.; Hastings, J. W.; Wilson, T.; Viviani, V. R.
Abstract: Fungus‐gnats of the genus Arachnocampa are unique among bioluminescent insects for displaying blue–green bioluminescence, and are responsible for one of the most beautiful bioluminescence spectacles on the roofs of the Waitomo Caves. Despite morphological studies showing that Arachnocampa larval lanterns involve specialization of the Malpighian tubules, the biochemical origin of their bioluminescence remains enigmatic. Using a cDNA library previously constructed from lanterns of the New Zealand glowworm A . luminosa, we carried out the first transcriptional analysis of ~ 500 expressed sequence tags (ESTs) to identify putative candidate proteins for light production, and to better understand the molecular physiology of the lanterns and their relationship with Malpighian tubule physiology. The analysis showed an abundance of hexamerin‐like proteins, as well as luciferase‐like enzymes, indicating a possible critical role for these proteins in bioluminescence. These findings were corroborated by proteomic analysis of lantern extracts, which showed the presence of hexamerins and luciferase‐like enzymes. Other gene products typical of Malpighian tubules, such as detoxifying enzymes, were also found. The results support the existence of an evolutionary link between Malpighian tubule detoxification and the origin of bioluminescence in these Diptera. Copyright © 2015 John Wiley & Sons, Ltd.